P613 Predictors of treatment persistence in ulcerative colitis patients treated with golimumab: A multicentre cohort study. (16th January 2018) - Biscaglia, G; Savarino, E; Variola, A; Furfaro, F; Ferracane, C; Rizzati, G; Scaldaferri, F; Mocci, G; Buda, A; Privitera, A; Geccherle, A; Fiorino, G
Abstract: Background: Golimumab is an effective and safe therapy in moderate-to-severe ulcerative colitis (UC). Data from the PURSUIT trial show that up to 49% of patients maintain clinical response through Week 54. However, there is no clear evidence from medical literature about predictive factors of response. This study aimed to profile the best UC patient who may benefit from golimumab long-term treatment. Methods: A retrospective cohort study was conducted among 8 Italian Center. All consecutive patients receiving golimumab between January 2015 and November 2017 were evaluated. The primary outcome was to assess the treatment persistence and efficacy. Gender, age, previous and concomitant therapies, UC extension and severity, golimumab maintenance regimen and inflammatory biomarkers were investigated as predictors. Safety was also assessed. All the analyses were considered statistically significant for p < 0.05. Results: One hundred seventy-two UC patients were enrolled. Baseline characteristics are shown in Table 1. Median survival time was 15 months. Treatment persistence and efficacy was 91% at Month 2 ( n = 156), and 52% at Week 12. Only five patients (2%) had adverse events leading to drug discontinuation. Lower global Mayo score at baseline (OR 0.68, CI 95% 0.57–0.80, p < 0.001), lower endoscopic Mayo subscore (OR 0.56, CI 95% 0.33–0.97, p = 0.03), no previous use of biologics (OR 0.54, CI 95% 0.30–0.98, p = 0.042), no previous infliximab (OR 0.46, CI 95% 0.25–0.9, p = 0.01) were independently associated with treatment persistence at follow-up time. At multivariable analysis, lower Mayo endoscopic subscore (OR 0.62, CI 95% 0.52–0.76, p < 0.001) and no previous exposure to infliximab (OR 0.41, CI 95% 0.20–0.86, p = 0.01) were associated to treatment persistence. Conclusions: This real-life, large, multicentre cohort study confirmed that golimumab is effective and safe in moderate-to-severe UC. Moreover, UC patient with lower endoscopic Mayo subscore at baseline and no previous exposure to infliximab seems to be the best candidate to respond to golimumab in the long term.